Дослідження ефективності автоматизованої системи сніготанення на базі нагрівального кабелю в умовах житлового будинку - Крутофал, Олександр Сергійович; Milto, Oleksandr (ЦНТУ, 2025)
У роботі розглядаються принципи побудови систем сніготанення, характеристики нагрівальних кабелів, алгоритми автоматизованого керування та фактори, що впливають на економічні показники системи. Також проведено порівняльний аналіз роботи автоматизованої та неавтоматизованої систем сніготанення, визначено потенціал зниження енерговитрат та підвищення безпеки експлуатації об’єкта. The paper examines the principles of snow melting systems construction, characteristics of heating cables, automated control algorithms and factors affecting the economic performance of the system. A comparative analysis of the operation of automated and non-automated snow melting systems was also conducted, and the potential for reducing energy consumption and increasing the safety of the facility's operation was determined.
Research on the effectiveness of an automated snow melting system based on a heating cable in a residential building
Keywords: автоматизована система сніготанення; нагрівальний кабель; житловий будинок; automated snow melting system; heating cable; residential building